Evaluation of antioxidant activities of various extracts from Dialium indium var. indium L. fruits - Osman, Muhamad Faris; Mohd Hassan, Norazian; Khatib, Alfi; Tolos, Siti Marponga (2017)
Dialium indum var. indum L. (family Fabaceae) or keranji is a wild plant native to Southeast Asia. In Malaysia, the fruit has gained its popularity through its inclusion in a traditional Malay poem, namely pantun. To date however, the fruit of D. indum is considered as underutilized because its use is limited to consumption as seasonal sweets by the locals. Hence, this study aimed to determine the antioxidant activities of various extracts of exocarp, mesocarp, and seed of D. indum fruit by using cupric ion reducing antioxidant capacity (CUPRAC) and linoleic acid peroxidation inhibition assays. The results indicated that the seed consecutive methanol (SCM) extract had highest reducing power (1515.78 ± 75.86 µmol Trolox Equivalent (TE)/g dry extract). However, exocarp consecutive hexane (ECH) extract possessed highest anti-lipid-peroxidation (IC50 102.63 ± 5.15 µg/mL), comparable to the standard quercetin (IC50 43.73 ± 2.59 µg/mL). The results indicated that the seed possessed highest total antioxidant capacity while the lipid-soluble antioxidants were concentrated mostly in the exocarp. This study evidenced that the seed and exocarp of D. indum fruit are good sources of antioxidants, which are useful properties in protection of macromolecules in the body against deleterious effects of oxidative stress.